Reiki efficacy of therpy in improving pain, fatigue, quiality of life and its impact on activities´s of women daily living suffering from fibromyalgia - Lourdes Casillas Santamaría; Pilar Palazuelos Puerta; Irene de Blas Gómez; Ana Asenjo Montoro; Patricia Latorre Marco; Isabel Díaz Espinos (Fundación para el Desarrollo de la Enfermería, 2013)
Objective: The evaluation the Reiki therapy effectiveness to relieve pain, fatigue and its impact on activities´s of women daily living suffering from fibromyalgia.Methods: A controlled clinical trial, randomized to three groups (Reiki therapy, placebo and control) and hiding of random distribution. Subjects: 150 women, over 18 years, diagnosed with fibromyalgia, according to the American College of Rheumatology (ACR), diagnosed for more than a year and signing the informed consent. It will exclude those with mental or cognitive impairment that could impede their participation. Scope: Fibromyalgia Association of Madrid, with a record 2,500 members, with headquarters in downtown Madrid. Intervention: Standardization of Reiki therapy's interventions, and placebo control. Reiki therapy will be applied by a solo Reiki Master, the placebo group will be attended by one solo nurse with no experience of touch therapy, simulating touches points of energy in the body; the control group receive no intervention. It will be 4 weekly sessions of 60 minutes in the case of Reiki and placebo groups. Participants in the control group will have to go to school to complete the questionnaires in the same periods of time. Variables (measuring instruments): main outcome variable: pain. It will be collected data on pain throughout the study (VAS), fatigue (VAS), quality of life (SF-36) and disease impact on activities of daily living (FIQ) at various times: at the studio's beginning (baseline), after a month and 3 months later. Sociodemographic and clinical variables will be collected also. Analysis: It will be made by allocated treatment (intention to treat). Comparisons shall be made of pain, fatigue, quality of life and disease's impact on daily life activities among the three groups. Statistical analysis was done by analysis of variance.